Infection of Dendritic Cells With Mycobacterium avium subspecies hominissuis Exhibits a Functionally Tolerogenic Phenotype in Response to Toll-Like Receptor Agonists via IL-10/Cox2/PGE2/EP2 Axis - Kim, Woo Sik; Yoon, Joo-Heon; Shin, Min-Kyoung; Shin, Sung Jae (Frontiers in Microbiology, 2019)
Mycobacterium avium subspecies hominissuis(MAH) is the most common agent causing nontuberculous mycobacterial disease in humans. It mainly causes chronic and slowly progressive pulmonary disease (PD), which requires a long-term treatment, and allows opportunistic co-infection by common pulmonary pathogens such as Pseudomonas aeruginosa, Staphylococcus aureus, and Aspergillus spp., thereby resulting in alteration of host immune response. In the present study, we investigated the phenotypical and functional alterations of dendritic cells(DCs), a bridge antigen-presenting cell between innate and adaptive immunity, following MAH infection in response to various toll-like receptor(TLR) agonists mimicking co-infection conditions, along with subsequent T cell response. Interestingly, MAH-infected DCs produced interleukin(IL)-10 significantly and decreased the level of IL-12p70 in response to Poly I:C and LPS, although not so in response to Pam3CSK4, imiquimod, or CpG oligodeoxynucleotide, thereby indicating that the TLR3 and TLR4 agonists functionally altered MAH-infected DCs towards a tolerogenic phenotype. Moreover, IL-10-producing tolerogenic DCs were remarkably induced by MAH and P. aeruginosa co-infection. To precisely elucidate how these TLR agonists induce tolerogenic DCs upon MAH infection, we sought to clarify the major mechanisms involved, using LPS, which caused the greatest increase in IL-10 production by the TLR agonists. Increased IL-10 stimulated the creation of tolerogenic DCs by significantly reducing MHC class II expression and MHC class II-antigen presentation, eventually inhibiting CD4+ T cell proliferation, along with decreased IFN- and IL-2. The tolerogenic phenotypes of MAH/LPS-treated DCs were restored by anti-IL-10 neutralization, validating the induction of tolerogenicity by IL-10. Interestingly, IL-10-producing-tolerogenic DCs were observed after infection with live MAH, rather than with inactivated or dead MAH. In addition, TLR2-/-and TLR4-/-DCs confirmed the association of IL-10 production with TLR2 and TLR4 signaling; IL-10 production synergistically increased when both TLR4 and TLR2 were involved. Expression of Cox2 and PGE2 increased along with IL-10 while that of IL-10 was inhibited by their selective inhibitors celecoxib and anti-EP2 antibody, respectively. Thus, the tolerogenic phenotypes of MAH/LPS-treated DCs were proven to be induced by Cox2/PGE2-dependent EP2 signaling as the main mechanism. These findings may provide important clues that the tolerogenic cascade in MAH-infected DCs induced by TLR4 signaling can alter host immune response.